The Significance of Monitoring Serum and Faecal Calprotectin in Healthy Dogs - Fialkovičová Maria; Benková Marta; Tóthová Csilla; Kejr Kristin Maria; Kunay Lukáš; Gomulcová Simona; Horňáková Ľubica; Karasová Martina; Bielik Bohumil; Takáčová Martina; Weissová Tatiana (Folia Veterinaria)
The aim of this study was to monitor the concentrations of serum and faecal calprotectin in healthy dogs, determine confidence intervals, and observe its dependence on factors such as age. This study included 70 dogs representing 16 breeds, including samples collected from small and medium sized mixed breeds. All dogs were fed dry kibble. The concentrations of calprotectin in serum and faeces were measured using the Quantitative Sandwich ELISA kit from MyBioSource, specifically designed for canine samples. Faecal sample preparation followed the manufacturer’s instructions for the specific canine ELISA test, and the obtained concentrations of serum and faecal calprotectin were divided into groups in relation to age. The first group consisted of individuals up to one year of age and one-year-old dogs. The following groups consisted of dogs of age 2‒4 years, 5‒7 years, 8‒9 years, and 10‒12 years. Monitoring the faecal calprotectin in healthy dogs showed a range of values from 2.63 to 28.81 ng.ml-1, while serum calprotectin concentrations ranged from 3.23 to 13.51 ng.ml-1. The statistical analysis confirmed that calprotectin levels in faeces and serum did not differ significantly across different ages. However, when the monitoring calprotectin concentrations in serum and faeces of healthy dogs was based on weight, the dogs were divided into groups according to size. The group with large dog breeds consisted of individuals over 20 kg (n = 15), the group with medium-sized dogs included individuals weighing between 12 kg and 20 kg (n = 16), and the largest group consisted of small dog breeds under 12 kg (n = 39). Statistical analysis confirmed a significant difference when comparing faecal calprotectin levels based on the size of dogs, but the serum calprotectin concentrations did not differ significantly with respect to dog size. Based on these calculations, confidence intervals for faecal calprotectin and serum calprotectin in healthy dogs ranged from 10.96 to 15.14 ng.ml-1 and 7.96 to 8.49 ng.ml-1, respectively. Since this is the first study on calprotectin in serum and faeces of healthy dogs using the mentioned ELISA test, further studies on larger numbers of dogs will be needed in the future.